A road tunnel model for the systematic study of lighting situations. (February 2018) - Renzler, M.; Reithmaier, N.; Reinhardt, R.; Pohl, W.; Ußmüller, T.
Abstract: In this study we employ a road tunnel model to simulate the crossing in a car at variable speeds using running LED-lights. Different lighting situations were created, namely symmetric-, counterbeam- and probeam lighting and were measured using a luminance camera. The results show that probeam lighting yields a much better object illumination than counter-beam- and symmetric-lighting while consuming the same amount of power as symmetric- and counterbeam lighting due to use of LED-technology. Based on this we argue that probeam lighting is a viable alternative to the commonly used counterbeam lighting in the interior zone of road tunnels.